Uncovering the species diversity of subterranean rodents at the end of the World: three new species of Patagonian tuco-tucos (Rodentia, Hystricomorpha, Ctenomys) - Teta, Pablo Vicente (2020)
Ctenomys Blainville 1826 is one of the most diverse genera of South American caviomorph rodents. Currently, six species of this genus are reported from Patagonia, south of 42◦S. In this contribution, we assessed the taxonomic status of several populations from eastern and central Chubut province, northern Patagonia. Based on phylogenetic analyses of DNA sequences, morphology assessment (qualitative and quantitative), and previously published karyological data, we describe three new species of this genus, one formed by two subspecies, endemic to northern Patagonia. In addition, we include C. coyhaiquensis Kelt and Gallardo 1994 into the synonymy of C. sericeus J.A. Allen 1903. Finally, we discussed the need for additional integrative approaches, including field collection of specimens, to better understand the diversity of this highly speciose rodent genus.